The Kemampuan Komunikasi Matematis Siswa Ditinjau Dari Self Confidence Pada Siswa Kelas VIII A SMP Negeri 2 Pringgarata Tahun Ajaran 2023/2024 - Ihsan, Lalu M. Izzuddin Izmi Ihsan; Sri Subarinah; Nilza Humaira Salsabila; Nyoman Sridana (FKIP Universitas Mataram, 2024)
Mathematical communication skills are students' ability to process vocabulary, notation and mathematical structures both in the form of reasoning, representation and problem solving in mathematics. This research aims to describe the mathematical communication skills of class VIII A students of SMP Negeri 2 Pringgarata in the 2023/2024 academic year with high and low self-confidence. The type of research used is qualitative descriptive research. The research results showed that (1) students with high self-confidence are able to interpret mathematical ideas in writing both in the form of reasoning, representation, and solving mathematical problems using appropriate mathematical terms and are able to fulfill all indicators of mathematical communication, namely presenting symbols, creating mathematical models, and write. (2) Students with low self confidence are only able to create mathematical models. Students with low self-confidence are not yet able to interpret mathematical ideas in writing either in the form of reasoning, representation, or solving mathematical problems using appropriate mathematical terms.